Politically motivated intergovernmental transfers in Russia: The case of the 2018 FIFA World Cup - Ekaterina Paustyan (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
This paper studies the distribution of politically motivated intergovernmental transfers in Russia focusing on the case of the 2018 FIFA World Cup. It investigates what factors have accounted for the selection of the 2018 FIFA World Cup venues. Qualitative Comparative Analysis of 14 cases reveals that well-connected political elites were able to secure the right for their regions to host the championship and, as a result, to extract additional funds from the center. These findings are in line with the argument that the regional governments in Russia play an important role in the distribution of politically sensitive transfers. Taking into account that these transfers have been increasing over the past years, there is no surprise that the regional elites have developed various lobbying strategies and mechanisms for attracting them.
URN:NBN:fi:bof-202101291081
Keywords: E62; L83; O23; P26; R11; 330; Russia; politically sensitive transfers; Qualitative Comparative Analysis